HIV testing rates among pregnant women in Managua, Nicaragua, 2010-2011 Tasas de realización de pruebas de detección del VIH en mujeres embarazadas en Managua, Nicaragua, 2010-2011 - Jonathan Colasanti; Marco Lorio Rugama; Karina Lifschitz; Manuel Largaespada; Benito Flores-Lopéz; Christopher Dodd; Daniel J. Feaster; Margaret Pereyra; Lisa R. Metsch (Pan American Health Organization, 2013)
OBJECTIVE: To determine and report the rate and pattern of HIV testing among pregnant women receiving ambulatory prenatal care, and the total number of positive cases in pregnant women in Managua, Nicaragua. METHODS: A retrospective epidemiological review was conducted to assess HIV testing rates among pregnant women in Managua attending district-level health centers in 2010 and 2011, with a focus on a single district (District 6.1). RESULTS: A total of 39.4% of pregnant women receiving prenatal care at Managua health centers in 2010 received an HIV test, and this number increased to 49.8% in 2011 (P < 0.001; phi statistic, 0.10). In 2010, 27 pregnant women in Managua were found to be HIV positive, corresponding to 0.17% of those who were tested. In 2011, 31 tested positive (0.12% of those who were tested). Comparisons between 2010 and 2011 at the District 6.1 level reflect an increase in women who received HIV tests from 24.2% in 2010 to 49.3% in 2011 (P < 0.001; phi statistic, 0.26). In District 6.1, two pregnant women were identified as HIV positive in 2010 and three in 2011, corresponding to 0.32% and 0.13% of pregnant women tested, respectively. CONCLUSIONS: Despite significant improvements in HIV testing rates from 2010 to 2011, the numbers tested remain below the goal recommended by the Pan American Health Organization (PAHO) in order to achieve virtual elimination of mother-to-child transmission by 2015 (> 95%). Patterns of testing demonstrated increased rates coinciding with a health fair in District 6.1, but effects were short-lived. Therefore, new approaches are necessary to bolster prenatal HIV screening efforts within Managua and District 6.1 in Nicaragua. OBJETIVO: Determinar y notificar la tasa de realización de pruebas de detección del VIH, los patrones obtenidos y el número de casos positivos en las mujeres embarazadas que recibieron asistencia prenatal ambulatoria, en Managua, Nicaragua. MÉTODOS: Se llevó a cabo un examen epidemiológico retrospectivo para evaluar las tasas de ...